The Influence Of Rme-Based Teaching Media Assisted By The Pixton Application On Students' Interest In Learning Mathematics - Pratiwi, Suchi; Novika Sukmaningthias; Sari, Novita (JTMT: Journal Tadris Matematika, 2023)
The type of research conducted was quantitative research using quasi-experimental methods and The Pretest-Posttest Non-Equivalent Control Group design with the aim of knowing significant differences between RME teaching media assisted by the pixton application and conventional teaching media on students' interest in learning mathematics and which learning media is more affective . The samples used were students of class VIII.2 as the control class and students of class VIII.6 as the experimental class. The data collection process uses a questionnaire using a Likert scale, where the Likert scale is an ordinal scale, so the data analysis uses non-prametric statistics Mann Whitneyy U test. Based on data analysis with the Mann-Whitneyy U test, Asymp.Sig values are obtained (2- tailed) is 0.029. This significance value is less than 0.05 which results in H0 being rejected and H1 being accepted. So from this analysis it can be concluded that learning media based on Realistic Mathematics Education assisted by the pixton application is proven to be more affective in increasing students' interest in learning mathematics in SPLDV material compared to conventional learning.